STEM-02. GENERATION AND CHARACTERISATION OF A LIVING BIOBANK OF POST-SURGICAL RESIDUAL GLIOBLASTOMA TO IDENTIFY NOVEL THERAPEUTIC TARGETS. (14th November 2022) - McGarrity - Cottrell, Connor; Myers, Katie; Wang, Dennis; Dunning, Mark; Bagga, Veejay; Al-Tamimi, Yahia; Sinha, Saurabh; Rominiyi, Ola; Collis, Spencer
Abstract: Glioblastoma is the most common cancer arising within the brain and contributes to 190, 000 brain tumour related deaths/year globally. Current standard-of-care therapy consists of maximal safe surgical resection, radiotherapy with concomitant then adjuvant chemotherapy (Temozolomide) which triggers the cellular DNA damage response (DDR). However, survival for patients remains poor (median OS 12-15 months). Lack of progress in the development and clinical translation of novel therapeutics is largely attributed to extensive inter- and intra-tumoral heterogeneity and resistant glioma stem cell (GSC) niches. Traditionally, primary ex vivo and in vivo models of glioblastoma have been derived from the resected tumour mass potentially omitting significant genetic, epigenetic and phenotypical characteristics exhibited by post-surgical residual tumour cells that are ultimately responsible for disease recurrence and morbidity. We therefore hypothesise that GSC's isolated from the invasive edge of the tumour are inherently treatment resistant due to an increased "stemness" and upregulated DDR. Here we display novel methodology for the generation of multiple parallel primary ex vivo GSC cell models from anatomically discrete regions of specific partial lobectomy specimens. Importantly, these samples contain large portions of infiltrated adjacent brain to recapitulate features of resected (tumour core) and typically residual glioblastoma (distal invasive tumour edge). Initial RNA-seq analysis has revealed large divergent transcriptional landscapes of resected vs residual tumour cells and protein expression analyses has identified key differences in DDR proteins and subsequent cellular responses to current standard-of-care radio-chemotherapy regimens. Immunofluorescence analysis of DNA damage markers has also revealed differential capacity & kinetics for repair of DNA damage between resected and residual GSC populations. These data therefore highlight the potential clinical relevance of our novel parallel resected and residual ex vivo glioblastoma models, which will hopefully aid evaluation of novel therapeutics capable of targeting post-surgical GSC subpopulations leading to improved disease outcomes.